Using Project-based Teaching to Improve Students’ Confidence in English Presentation Skills at a High School in Bac Ninh Province = Đánh giá của giáo viên và học viên về giáo trình English Unlimited A1-Starter tại một trường trung cấp Công an n - Nguyen, Thi Thuy Dung (2019)
It is obvious that project-based learning plays an important role in language teaching and learning. This thesis was conducted with the aims to find out the reasons why students lack confidence in presentations, explore students’ and teacher’s attitudes toward the project-based learning, and explore how the projectbased learning lessons help improve ten – grade students’ confidence in English presentation skills.